اثر خروج بريطانيا من الاتحاد الاوروبي وتداعياته 2021م: دراسة تحليلية (Journal of Academic Research, 2025)
Abstract:This analytical study examines the reasons and motivations that led to the United Kingdom's exit from the European Union (Brexit), in addition to reviewing the political, economic, and social repercussions of this decision at the British and European levels. The researcher focuses on the basic premise that Brexit was neither a sudden nor an isolated event, but rather the result of historical, cultural, political, and economic accumulations that prompted the British people to vote in favor of leaving by over 51% in the 2016 referendum.The study highlights the most important reasons that prompted Britain's withdrawal, such as disputes over national sovereignty, European restrictions on domestic policies, concerns about immigration, and declining confidence in European institutions. The study also examines the direct impacts, such as market volatility, the decline in the value of the pound, and the rise of separatist calls in Scotland and Northern Ireland, as well as the resignation of Prime Minister David Cameron. At the European level, the researcher analyzes the implications of Brexit for the future of the European Union, both in terms of the balance of political and economic power and the potential for other countries to take similar steps, threatening the cohesion of the European project itself. The study adopts a descriptive analytical approach and draws on official and academic data and references. It concludes with a conclusion confirming that Brexit represents a major strategic shift in the European and global order, one that will have long-term repercussions that require a reconsideration of the nature of European and international alliances.